SPE Oil and Gas India Conference and Exhibition 2010
DOI: 10.2118/129002-ms
|View full text |Cite
|
Sign up to set email alerts
|

Novel Microbial Process for Mitigating Wax Deposition in Down hole Tubular and Surface Flow Lines

Abstract: Many oil fields producing waxy crude, face severe wax deposition problem in down hole tubulars and surface flow lines. Sometimes this problem is also encountered at the face of producing zone in the well bore region due to changes in temperature & pressure conditions. This problem frequently results in complete blockage of the crude passage and poses severe production problem. Conventional methods such as thermal, magnetic, mechanical scraping, solvent cleaning and chemical treatment etc. are not only cumberso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Biological wax removal methods have been thoroughly investigated in recent years by several researchers. The results attained by Rana et al showed that the developed bacterial systems of paraffin-degrading bacteria with nutrient supplements and growth enhancers could eliminate the need for repeated scrapings of wax over a period of several months (Rana et al 2010). If successfully implemented, these methods have the benefit of providing continuous control of wax deposition through constant biodegradation, instead of just providing a temporary solution.…”
Section: Bacterial Treatmentmentioning
confidence: 99%
“…Biological wax removal methods have been thoroughly investigated in recent years by several researchers. The results attained by Rana et al showed that the developed bacterial systems of paraffin-degrading bacteria with nutrient supplements and growth enhancers could eliminate the need for repeated scrapings of wax over a period of several months (Rana et al 2010). If successfully implemented, these methods have the benefit of providing continuous control of wax deposition through constant biodegradation, instead of just providing a temporary solution.…”
Section: Bacterial Treatmentmentioning
confidence: 99%
“…The specic heat and molecular thermal conductivity of the mixture uid are evaluated based on the pseudo-components specic values as done for the molecular viscosity, see Eqs. (8) and (9); the turbulent thermal conductivity is computed as λ t = c p µ t /Pr t , where…”
Section: Governing Equationsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] Several traditional methods are used for removing the accumulated wax deposit from the inner wall of a pipeline, such as mechanical removal (pigging), [19][20][21][22] inductive heating, 23 biological treatment (hydrochloric acid, paraffin solvents). [24][25][26][27][28] Regular pigging is the most effective and common way for removal of the wax deposits in pipelines. [20][21][22][23] A mechanical pig driven by the differential pressure of the oil flow, usually equipped with rubber sealing discs or brushes as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%